Emerging technology as a platform for market shaping and innovation - Valtteri Kaartemo; Anna-Greta Nyström (Elsevier, 2022)
Market shaping literature portrays markets as outcomes of deliberate and designed actions. While technological development might accelerate changes in the market, market-shapers do not often develop technology themselves. As they rely on complementary technologies, enabling new ways to integrate resources and co-create value, the field has not paid particular attention to the role of technology in market shaping and innovation. To advance the literature, we conceptually differentiate between technology “as a market offering” and “as a platform for market shaping and innovation”. Through incorporating a structured Delphi study on the impact of 5G technology on the healthcare market, we identify nine important and probable market changes induced by 5G. We contribute to research on market change by highlighting a broad inclusion of market actors for a more holistic view of market changes introduced by emerging technology.